2022
DOI: 10.3390/ijerph19031388
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Social Inequalities in Awareness of Coronary Artery Disease in European Countries

Abstract: Coronary artery disease (CAD) is the single leading cause of death in Europe and the most common form of cardiovascular disease. Little is known about awareness in the European population. A cross-sectional telephone survey of 2609 individuals from six European countries was conducted to gather information on perceptions of CAD, risk factors, preventive measures, knowledge of heart attack symptoms and ability to seek emergency medical care. Level of awareness was compared according to gender, age, socioeconomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Awareness of CVDs as the major future health issue was significantly lower amongst female patients. Our finding is in line with that of a recent cross-sectional telephone survey involving 2609 individuals without chronic diseases from six European countries [40]. In general, women attribute much less importance to heart disease than it warrants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Awareness of CVDs as the major future health issue was significantly lower amongst female patients. Our finding is in line with that of a recent cross-sectional telephone survey involving 2609 individuals without chronic diseases from six European countries [40]. In general, women attribute much less importance to heart disease than it warrants.…”
Section: Discussionsupporting
confidence: 91%
“…The educational level did not emerge as a major determinant of knowledge of cardiovascular disease risk. Conversely, different studies conducted on the general population demonstrated a strong association between higher education and better health literacy [21,40]. The most likely explanation of our finding is that among the TM population, the frequent doctor-patient encounters represent the most important source of medical information, compensating for education-induced biases.…”
Section: Discussionmentioning
confidence: 50%
“…111,112 Yet, women are five times less likely to have a diagnosis considering heart disease as the main health issue or leading cause of death and they are significantly less likely to have ever received a cardiovascular screening test as well. 113 Hence, diagnostic and treatment inequalities between men and women need to be urgently improved.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, even though men develop CVD earlier in life, women catch up after menopause and therefore the lifetime risk of CVD is similar for both men and women if estimated for a total life span 111,112 . Yet, women are five times less likely to have a diagnosis considering heart disease as the main health issue or leading cause of death and they are significantly less likely to have ever received a cardiovascular screening test as well 113 . Hence, diagnostic and treatment inequalities between men and women need to be urgently improved.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…There are two points that cannot be ignored. The awareness rate of IHD risks is lower than the prevalence rate ( Garrido et al, 2020 ; Daponte-Codina et al, 2022 ), and the difficulty in treating ischemia comes from poor regeneration of cardiomyocytes after IHD and myocardial infarction (MI). Although the myocardium of the patients with chronic coronary syndrome has been damaged, the tolerance of myocardial cells to ischemia increases due to the formation of coronary collateral circulation.…”
Section: Introductionmentioning
confidence: 99%